Numerical solution of coupled Schrödinger–KdV equation via modified variational iteration algorithm-II - Safavi, Mostafa (SeMA journal, 2018)
This paper applied the modified variational iteration algorithm-II to obtain the numerical solution of coupled Schrödinger–KdV equation. For this purpose, we use the Jacobi periodic solution and Soliton solution as initial guess for a better approximation. Numerical results and comparison exact and approximate solution have demonstrated that modified variational iteration algorithm-II is very effective and convenient for nonlinear equations, especially for the coupled Schrödinger–KdV equation.